Multiculturalism in Asia: Peace and Harmony by Imtiyaz Yusuf - Mohd Al Adib Samuri (Kajian Malaysia, 2020)
This book that was edited by Imtiyaz Yusuf comes at a crucial time to forward the narrative that all major religions and cultures, especially in Asia, recognise the religious and cultural diversity within communities in pursuance of peaceful co-existence. Imtiyaz Yusuf provocatively states at the beginning of the book that the recent global rise in conflict, xenophobia and ethnoreligious exclusivism in many regions including Southeast Asia is a growing concern for the survival of the multicultural world. This book offers significant insights into multiculturalism in the Asian context, primarily from the perspective of religion (Buddhism, Islam, Hinduism and Christianity), politics, sociology, anthropology, and also economics by incorporating the epitome of the challenges, the conflicts and the successes of implementing policies of multiculturalism in Asian countries.